1982
DOI: 10.1007/bf01716244
|View full text |Cite
|
Sign up to set email alerts
|

Cyanide toxicity of sodium nitroprusside in therapeutic use with and without sodium thiosulphate

Abstract: Sodium nitroprusside (SNP) as a mono-infusion was administered to 51 patients for periods of a few hours. A further group of 19 patients received SNP for periods of several days as a combination solution of SNP mixed with sodium thiosulphate. The concentrations of cyanide and of thiocyanate in the blood of all patients were measured. In seven of the patients the level of thiosulphate was also measured. Infusion of SNP on its own at levels exceeding 2 microgram/kg/min led to the rising of cyanide levels in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
42
0

Year Published

1988
1988
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(43 citation statements)
references
References 37 publications
1
42
0
Order By: Relevance
“…found an apparent volume of distribution of 50% body weight, whilst Experiments [5][6][7][8] The analyses early in the course of these studies, appeared to confirm the findings of the earlier study and show first-order kinetics, but later the semilogarithmic plot deviated from a straight line and entered a second phase of much slower elimination (Figure 2). The second phase started at 75-80 min.…”
Section: Introductionmentioning
confidence: 53%
“…found an apparent volume of distribution of 50% body weight, whilst Experiments [5][6][7][8] The analyses early in the course of these studies, appeared to confirm the findings of the earlier study and show first-order kinetics, but later the semilogarithmic plot deviated from a straight line and entered a second phase of much slower elimination (Figure 2). The second phase started at 75-80 min.…”
Section: Introductionmentioning
confidence: 53%
“…The toxicity of SNP and its major metabolite, cyanide (CN -), was previously explored in nonchronobiological investigations in rodents and others mammals [37][38][39]. The subcutaneous administration of SNP to mice produced similar signs of toxicity described above, that were revealed by others authors when studying CN -toxicity in mice [39][40].…”
Section: Discussionmentioning
confidence: 83%
“…The physical compatibility of this mixture was also re-confirmed and is consistent with the previous literature. 5 A novel quantitative HPLC method for the determination of nitroprusside, thiosulfate, and thiocyanate in solution is also presented.…”
Section: Discussionmentioning
confidence: 99%
“…To combat cyanide toxicity, thiosulfate can be administered with nitroprusside, which has been demonstrated to have equal efficacy in the treatment of hypertensive crises 5 and cerebral vasospasm, 6 with no adverse events reported. A recent prospective randomized trial demonstrated equal blood pressure control between nicardipine and nitroprusside in neurosurgery patients.…”
mentioning
confidence: 99%
See 1 more Smart Citation